Cell-mediated immune response in vitro. II. The role of thymus and thymus-derived lymphocytes. - Wagner, H; Harris, A; Feldmann, M (1972)
A recently developed allograft system for the generation of a cell-mediated response in tissue culture was applied to an analysis of the cells involved in that response. Lymphoid cells from CBA mice (H-2k) were immunized in vitro with mitomycin-treated BALB/c (H-2d) spleen cells and the cell-mediated response measured by lysis of 51Cr-labeled P815 mastocytoma cells (H-2d). It was found that in mouse spleen the precursor of cytotoxic lymphocytes, as well as the effector cells themselves are θ positive lymphocytes, a characteristic of T cells. Normal mouse thymocytes alone differentiate in vitro into cytotoxic effector cells, thus excluding a thymus bone marrow synergism in the allograft response in vitro. Various lymphoid cell populations were assayed as sources of precursor cells for the cell-mediated response. Purified splenic T lymphocytes were as active as cortisone-resistant thymocytes which were 10- 12-fold more active than thymus cells. Spleen lymphocytes were 3-fold more active. In vitro immunization of cortisone-resistant thymocytes resulted in the most active killer cell population. Fifty percent of the target cells were lysed within 150 min at a lymphocyte-to-target cell ratio of 1 to 1 or less. Such activity is higher than any previously reported from in vivo immunization procedures. © 1972.